Low circulating adiponectin and resistin, but not leptin, levels are associated with multiple myeloma risk: a case-control study. - Dalamaga, Maria; Karmaniolas, Konstantinos; Panagiotou, Anna; Hsi, Alex; Chamberland, John; Dimas, Cleanthi; Lekka, Antigoni; Mantzoros, Christos S (Cancer Causes Control, 2009)
Accumulating evidence supports a role for obesity in the etiology of multiple myeloma (MM). The distinct possibility exists that obesity may be linked to MM through altered adipokine secretion and circulating levels, one of which, adiponectin, has a protective role in several malignancies, including leukemia. In this case-control study, we investigated the role of serum adiponectin, resistin, and leptin levels in the etiopathogenesis of MM and we explored their association with several established prognostic factors. Seventy three patients with incident, histologically confirmed MM and 73 controls matched on gender and age were studied between 2001 and 2007, and blood samples were collected. Serum adiponectin, leptin, resistin, as well as MM prognostic parameters were determined. Statistical analysis of the data was performed using univariate and multivariate analyses. Lower serum adiponectin and resistin levels were associated with higher risk of MM by bivariate analysis and after adjusting for age, gender, BMI, and serum levels of leptin (p < 0.0001). Adiponectin may have a protective role in MM, whereas leptin was not associated with risk for MM at a comparable level of significance and resistin levels may be decreased via a compensatory mechanism. Further studies are needed to confirm these associations and to explore the mechanisms underlying adiponectin's role in MM and plasma cell dyscrasias.
Keywords: Adiponectin; Aged; Body Mass Index; Case-Control Studies; Enzyme-Linked Immunosorbent Assay; Female; Humans; Leptin; Male; Middle Aged; multiple myeloma; Obesity; Prognosis; Resistin; Risk Factors